A Comparative Fiqh Analysis of Online Buying and Selling Transactions: Perspectives of the Four Madhhabs in Madzāhibu al-Arba'ah - Khoirul Umam; Ali Romdhoni; Nurul Azizah; Moh Farhan; Ahmad Fatkhul Amin (UAS PRESS, 2026)
This study aims to examine and comparatively analyze the perspectives of the four Sunni madhhabs Hanafi, Maliki, Shafi'i, and Hanbali on online buying and selling transactions by referring to Madzāhibu al-Arba'ah by Abdurrahman Al-Juzairi, with a focus on identifying points of convergence and divergence relevant to contemporary digital commerce. While previous studies have generally addressed online transactions from a broad Islamic law perspective, few have conducted a systematic comparative analysis rooted in classical fiqh turath across all four madhhabs simultaneously. This study employs a normative qualitative library research method with a comparative fiqh approach, using Madzāhibu al-Arba'ah as the primary source and supported by contemporary fiqh muamalah literature, international journal articles on Islamic e-commerce, and relevant regulatory documents. Data were analyzed through descriptive-analytical and comparative methods to examine the pillars and conditions of sale, ijab-qabul, clarity of object, and the concept of ittihād al-majlis in online transactions. The findings reveal that all four madhhabs permit online buying and selling through analogical reasoning with bai' al-salam, yet differ significantly in their interpretations of sighat and ittihād al-majlis: the Hanafi and Hanbali schools adopt a more flexible stance on the form of ijab-qabul, the Shafi'i school emphasizes the continuity of the contract session and explicit sighah, while the Maliki school prioritizes public benefit through 'urf and maṣlaḥah mursalah. This study contributes a structured comparative framework that translates classical contract elements into their digital equivalents, offering normative guidance for Islamic e-commerce practice and sharia-compliant digital transaction governance.